2004
DOI: 10.1073/pnas.0400171101
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 is expressed on activated T cells as a costimulatory receptor

Abstract: Toll is the founder of a group of pattern recognition receptors that play a critical role in the innate immunity in Drosophila. At least 10 distinct Toll-like receptors (TLRs), recognizing pathogen-associated molecular patterns, have now been identified in humans. Most investigations on TLRs have focused on cells of the innate system. We report here that naïve human T cells expressed high levels of cellsurface TLR2 after activation by anti-T cell receptor antibody and IFN-␣. Activated cells produced elevated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

33
457
2
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 432 publications
(495 citation statements)
references
References 42 publications
33
457
2
3
Order By: Relevance
“…While the mechanism is still unclear and currently under investigation, this is in agreement with the previous findings that BLP preferentially promotes human and murine Th1 but not Th2 cell differentiation [7,8] and that TLR agonists selectively stimulate IFN-g but not IL-4 production by human gd T cells [9,10,12]. Our results therefore support current evidence and suggest the existence of a novel type I T-cell development pathway by directly recognising PAMP via TLRs on T cells.While human and murine T cells have the same ability in BLP recognition, the visualisation of LPS appears to be human CD8 1 T-cell specific, since human CD4 1 and murine CD8 1 T cells fail to do so [7]. This is in line with several reports that LPS stimulates murine CD8 1 T activation in vivo via an indirect pathway involving APC [17,18,26].…”
supporting
confidence: 92%
See 3 more Smart Citations
“…While the mechanism is still unclear and currently under investigation, this is in agreement with the previous findings that BLP preferentially promotes human and murine Th1 but not Th2 cell differentiation [7,8] and that TLR agonists selectively stimulate IFN-g but not IL-4 production by human gd T cells [9,10,12]. Our results therefore support current evidence and suggest the existence of a novel type I T-cell development pathway by directly recognising PAMP via TLRs on T cells.While human and murine T cells have the same ability in BLP recognition, the visualisation of LPS appears to be human CD8 1 T-cell specific, since human CD4 1 and murine CD8 1 T cells fail to do so [7]. This is in line with several reports that LPS stimulates murine CD8 1 T activation in vivo via an indirect pathway involving APC [17,18,26].…”
supporting
confidence: 92%
“…This was subsequently confirmed in mice [8]. Furthermore, human and murine memory T cells constitutively express surface TLRs and directly recognise TLR agonists [7,9,10]. Moreover, TLR agonists directly promote further TLR expression, survival and the function of NKT and gd T cells [11,12].…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…For example, it has been observed that homeostatic polyclonal activation of B cells, which results in the so-called serological memory, that is, detectable antibody to antigens that are no longer present in the host, can be induced/ maintained by TLR ligation (Bernasconi et al, 2002). Analogously, TLR2 is upregulated in CD4 þ T cells following TCR stimulation, and TLR2 ligands may thus provide an activation/maintenance signal in these cells (Komai-Koma et al, 2004). That signaling through TLRs in these aspects of B-cell responses requires NF-kB seems likely, but has yet to be demonstrated.…”
Section: T-cell Responses Mediated By Nf-kbmentioning
confidence: 99%